A tournament scheduling model for National Basketball Association (NBA) regular season games - HUA-AN LU; WEI-CHENG CHEN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to develop a mathematical programming model for the NBA tournament schedule that considers the equality of the teams that each team will face in the bracket. Professional sports leagues rely heavily on tournaments to maintain and grow their fan bases. However, there are many moving parts to consider when planning a tournament, including the dates, locations, opponents, and more.Methodology: To level the playing field between teams, an Integer Programming (IP) model was proposed. Results Numerical experiments showed that this model could improve the NBA’s tournament format.Novelty/Implications: To schedule the NBA’s professional sports tournaments in a balanced manner, a mathematical model has been proposed in this study. This model or the developed viewpoint can be used in various sports for tournament schedules.